Scleredema adultorum of Buschke over an unusual site associated with pregnancy - C Sujatha Vinod; H Ambika; Hariharasubramony Ambika; Nithya Reddy; Jayantha Kumar De (Wolters Kluwer Medknow Publications, 2014)
Scleredema adultorum of Buschke is characterized by symmetrical, diffuse, non-pitting erythematous swelling of the skin due to accumulation of collagen and mucopolysaccharides in the dermis. Herein we report a case of scleredema over an unusual site in a pregnant woman.